2015
DOI: 10.1371/journal.pone.0145953
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Second Generation Direct-Acting Antiviral Agents for Treatment Naïve Hepatitis C Genotype 1: A Systematic Review and Network Meta-Analysis

Abstract: BackgroundThe treatment of hepatitis C (HCV) infections has significantly changed in the past few years due to the introduction of direct-acting antiviral agents (DAAs). DAAs could improve the sustained virological response compared to pegylated interferon with ribavirin (PR). However, there has been no evidence from randomized controlled trials (RCTs) that directly compare the efficacy among the different regimens of DAAs.AimTherefore, we performed a systematic review and network meta-analysis aiming to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 29 publications
1
50
2
3
Order By: Relevance
“…Given the markedly improved efficacy, tolerability and safety of regimens that combine various directacting antiviral agents compared with regimens containing interferon, all patients would benefit from interferonfree therapy. 42,46,58,59 Therefore, interferonfree regimens are recommended as first line therapy for all indications.…”
Section: Direct-acting Antiviral Agents Given the Efficacy And Markedmentioning
confidence: 99%
“…Given the markedly improved efficacy, tolerability and safety of regimens that combine various directacting antiviral agents compared with regimens containing interferon, all patients would benefit from interferonfree therapy. 42,46,58,59 Therefore, interferonfree regimens are recommended as first line therapy for all indications.…”
Section: Direct-acting Antiviral Agents Given the Efficacy And Markedmentioning
confidence: 99%
“…In a systematic review on studies among people who inject drug (PWID) in Europe median of SVR was 55% ranged from 19% to 88% for PEG‐IFN plus RBV regimen . In a systematic review SVR12 among treatment naïve HCV genotype 1 in all DAA regimens without Peg‐IFN plus RBV ranged from 93% to 100% and in patients who received Peg‐IFN plus RBV was 48% . Two systematic reviews on interferon free treatment reported SVR12 in a range from 80% to 96% …”
Section: Discussionmentioning
confidence: 99%
“…Как правило, препараты ППД назначают в комбинациях -в виде двой-ной, тройной терапии, монотерапия не дает удовлетвори-тельных результатов. Для усиления эффекта препараты ППД также сочетают с комплексным ингибитором проте-аз ритонавиром, в качестве дополнительных компонентов в схемы могут включаться рибавирин (РИБ) и ПЭГ-ИФН, хотя это влечет рост частоты нежелательных явлений, особенно астенического синдрома и анемии [5].…”
Section: комбинацией софосбувира и даклатасвираunclassified